Methodologies for the Analysis of HCV-Specific CD4+ T Cells - Lokhande, Megha U.; Thimme, Robert; Klenerman, Paul; Semmo, Nasser (Frontiers in Immunology, 2015)
Virus-specific CD4+ T cells play a major role in viral infections, such as hepatitis C virus (HCV). Viral clearance is associated with vigorous and multispecific CD4+ T cell responses, while chronic infection has been shown to be associated with weak or absent T cell responses. Most of these studies have used functional assays to analyse virus-specific CD4+ T cell responses; however, these and other detection methods have various limitations. Therefore, the important question of whether virus-specific CD4+ T cells are completely absent or primarily impaired in specific effector functions during chronic infection, has yet to be analysed in detail. A novel assay, in which virus-specific CD4+ T cell frequencies can be determined by de novo CD154 (CD40 ligand) expression in response to viral antigens, can help to overcome some of the limitations of functional assays and restrictions of multimer-based methods. This and other current established methods for the detection of HCV-specific CD4+ T cells will be discussed in this review.